2019
DOI: 10.1111/cen.14002
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a preoperative prediction model for follicular thyroid carcinoma

Abstract: Objective The low pre‐ and intraoperative diagnostic rates in follicular thyroid carcinoma (FTC) often lead to inadequate surgical resection and necessitate further completion surgery. Therefore, the preoperative prediction of FTC in thyroid nodules is essential. Design and Patient Patients were categorized into two data sets: the modelling data set, which included 3649 patients admitted to our centre between January 2014 and December 2016, and the validation data set, which included 1253 patients admitted bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless, because of the considerable differences in the incidence rates, PTC accounted for the major subjects of these studies and FTC was slightly ignored. Recently, some researchers found that the patients with FTC had higher preoperative serum Tg level than those with non-FTC nodules [19]. In addition, other researchers found that higher preoperative Tg level was a potential diagnostic tool in patients with thyroid follicular neoplasm [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, because of the considerable differences in the incidence rates, PTC accounted for the major subjects of these studies and FTC was slightly ignored. Recently, some researchers found that the patients with FTC had higher preoperative serum Tg level than those with non-FTC nodules [19]. In addition, other researchers found that higher preoperative Tg level was a potential diagnostic tool in patients with thyroid follicular neoplasm [20][21][22].…”
Section: Discussionmentioning
confidence: 99%